Inoculação de Trichoderma asperellum (UFT-201) na cultura do Arroz (Oryza sativa) e Milho (Zea mays): alterações morfofisiológicas.fi - Luz, Lisandra Lima (Universidade Federal do Tocantins, 2025)
Brazilian agricultural production is considered one of the largest in the world, due to its territorial size and its potential to produce grains. Trichoderma spp. It is one of the most researched fungi in Brazil, as it occurs naturally in practically all types of soil, and because it has its own versatility of action, being able to act as a plant growth promoter. In view of this, the objective was to evaluate the efficiency of the inoculation of the UFT-201 isolate as a growth promoter in corn and rice crops in a greenhouse. The experiment was conducted at the experimental station of the Federal University of Tocantins (UFT) - Campus Universitário de Gurupi, located in the southern region of the state of Tocantins. Treatments consisted of five inoculant doses (0, 3, 6, 9, 12 g kg-1), mixed with the seed at sowing. The strain used was obtained from the collection of the laboratory of Applied Agromicrobiology and Biotechnology at the Federal University of Tocantins. The inoculant used was prepared in solid fermentation using rice as substrate. Morphological (height, root volume, dry mass) and physiological (photosynthetic pigments and gas exchange) characteristics were evaluated at 30 and 45 days after sowing. The fungus Trichoderma asperellum UFT-201 inoculated via seed increased root volume and biomass of corn and rice plants at a dose of 6 g kg-1 of seeds. The gain in crop biomass is related to physiological changes in crops promoted by inoculation and doses above 12 g kg-1 of seeds can reduce the initial development of crops, especially for rice. Key-words: Microorganism, Fungi, Agriculture, Growth Promotion.